1994
DOI: 10.1159/000201159
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Serum Soluble lnterleukin-2 Receptor, Soluble CD8 and Soluble CD4 in the Early Phases of Acute Pancreatitis

Abstract: When activated, lymphocytes secrete glycoproteins related to particular surface proteins, including soluble forms of the interleukin-2 receptor (sIL-2R) and of the surface proteins CD4 (sCD4) and CD8 (sCD8). We evaluated the release of these glycoproteins in order to assess the activation of the cellular immune system during the course of acute pancreatitis. Thirty-five patients with acute pancreatitis (22 M, 13 F, mean age 64 years, range 16-97) were studied. The diagnosis was based on typical abdominal pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 13 publications
0
25
0
1
Order By: Relevance
“…[3], The authors of both studies also noted that a sustained anergic state was associated with pancreatic septic complications. Recently, we ob served that in patients with acute pancreatitis there is a significant decrease in the absolute number of the periph eral total lymphocytes and their subpopulations [1], Fur thermore, in comparison with patients having the mild form of the disease, patients with severe acute pancreatitis had a significantly lower number of total, T and T-helper lymphocytes [1], We also reported low scrum values of soluble CD4 [9] thus suggesting an impaired activity of the CD4+ T lymphocytes. Table 2.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…[3], The authors of both studies also noted that a sustained anergic state was associated with pancreatic septic complications. Recently, we ob served that in patients with acute pancreatitis there is a significant decrease in the absolute number of the periph eral total lymphocytes and their subpopulations [1], Fur thermore, in comparison with patients having the mild form of the disease, patients with severe acute pancreatitis had a significantly lower number of total, T and T-helper lymphocytes [1], We also reported low scrum values of soluble CD4 [9] thus suggesting an impaired activity of the CD4+ T lymphocytes. Table 2.…”
Section: Discussionmentioning
confidence: 73%
“…sCD4. sCD8, TNF) have been found to be altered in patients with acute pancreatitis [3][4][5][6][7][8][9]. However, there are no data about lymphocyte proliferation in patients with acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced IL-2 production in experimental AP has recently been reported [148]. Moreover, soluble IL-2 receptor (sIL-2R) has been shown to be elevated in patients with severe AP than in healthy controls, and positively correlated with the severity of the attack [149]. Since released IL-2R is known to bind IL-2, it has been hypothesized that sIL-2R may act as an antagonist to IL-2-mediated cell responses, thus downregulating T-cell IL-2 production [149].…”
Section: Treatment Of Acute Pancreatitismentioning
confidence: 99%
“…It can combine with the membrane IL-2 receptor and then stimulates the maturity of T cells, enhances the function of natural killer cells and accelerates the secretion of immunoglobulins. Some authors 12) have found that soluble IL-2 receptors can competitively combine with IL2, resulting in the formation of an immunosuppressive complex and a decrease in the function of IL2. Although the mechanism and clinical significance of the elevation of sIL-2R levels after cardiac surgery is not clear, the decrease in IL2 and increase in sIL-2R are harmful for the immune defense system.…”
Section: Discussionmentioning
confidence: 99%